Pengaruh Struktur Aktiva Dan Tingkat Pertumbuhan Penjualan Terhadap Struktur Modal Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Rachma Eka Putri; Wida Fadhlia (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
The objective of this research is to examine the influence of the structure of assets and sales growth rate, both simultaneously and partially, toward the capital strucuture (empirical study on listed companies from the manufacturing sector at the Indonesia Stock Exchange). Years of observation of this research is 2008-2010. This type of research is a descriptive verificative. The data type used is secondary data gotten from the capital market reference center at the Indonesia Stock Exchange. The research method used in this research is purposive sampling method. Based on the criteria be obtained 114 companies as sample. The hypothesis is tested by using multiple linear regression analysis. The result of this research show that (1) the structure of assets and sales growth rate simultaneously have influence toward capital structure, (2) the structure of assets has positive influence toward capital structure, and (3) sales growth rate has positive influence toward capital structure.